The Influence of Brand Image, Brand Trust, Service Quality through Customer Satisfaction on Honda Brand Motorcycle Brand Loyalty in DKI Jakarta - Sugiearto Buntoro Theodore; Tony Sitinjak (Jurnal Indonesia Sosial Sains, 2024)
The automotive industry in Indonesia plays a crucial role in the country's economic development, with motorcycles being one of the most popular modes of transportation. Honda motorcycles have a significant market share among various brands due to their strong brand image, trust, and service quality. This study analyses the influence of brand image, trust, and service quality on Honda brand motorcycle brand loyalty through customer satisfaction in DKI Jakarta. Using a quantitative approach with a survey method, data was collected from 200 respondents who used Honda motorcycles in the DKI Jakarta area. Data was analysed using the Structural Equation Modeling (SEM) technique. The study results show that brand image, trust, and service quality significantly affect customer satisfaction, impacting brand loyalty. Customer satisfaction is essential to strengthening the relationship between independent variables and brand loyalty. These findings underscore the importance of improving service quality, strengthening the image, and building trust to create loyal customers for the Honda brand.